Stearyl amine-modified elastic cerosomes for boosting the anti-cancer activity of albendazole - Albash, Rofida; Azzazy, Hassan M. E.; Mosallam, Shaimaa; Hamed, Mohammed I. A.; Darwish, Khaled M.; Abdel-Fattah, Maha M.; Alshabani, Lama A.; Yousef, Einas M.; Selim, Heba Mohammed Refat M.; El-Fadaly, Ghadeer; Saleh, Asmaa; Aziz, Diana E. (Frontiers in Pharmacology, 2025)
BackgroundAlbendazole (ALB), originally developed as an anthelmintic agent, has been repurposed for use in cancer therapy. In the present work, ALB was incorporated into stearyl amine (SA)-based elastic cerosomes (EC) to improve its anticancer activity.MethodsStearyl amine elastic cerosomes containing albendazole (SA-EC-ALB) were formulated using the thin-film hydration method. A D-optimal experimental design was applied via Design-Expert® software (version 7) generating 19 formulations. The independent variables included SAA amount (X1), sonication time (X2), ceramide type (X3), and SAA type (X4), while the dependent variables were entrapment efficiency (EE%; Y1), particle size (PS; Y2), and polydispersity index (PDI; Y3).ResultsThe optimized SA-EC-ALB formulation, prepared with ceramide III and Pluronic L121 through sonication, achieved an entrapment efficiency (EE%) of 92.03 ± 3.53% and a particle size (PS) of 312.05 ± 9.32 nm. In-silico analysis indicated strong interactions between ALB and the vesicular components in water. Moreover, in-vivo evaluation of SA-EC-ALB antitumor activity, performed using the solid Ehrlich tumor model in adult Swiss albino male mice, demonstrated a significant reduction in tumor volume compared to the control group.ConclusionLoading ALB into SA-EC could potentially induce its anticancer effects.